Screening In Silico Alpha-amylase and Alpha-glucosidase Inhibitory Activity of Flavonoid Compounds for the Treatment of Type 2 Diabetes - Thanh Tung, Bui; Thi Huong, Le; Thi Duong, Trinh; Thi Huyen, Nguyen; Thi Thuy, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
Diabetes mellitus (diabetes) is a chronic disease associated with metabolic disorders and hyperglycemia. α-glucosidase and α-amylase, which play an important role in the hydrolysis of starch and carbohydrates, are enzymes. They are related to the increase and decrease in blood glucose levels. Flavonoids are a common group of natural compounds that have been shown to have many beneficial health effects. This study used molecular docking methods and drug-like criteria, predicting pharmacokinetics-toxicity (ADMET) to screen and evaluate potential flavonoid compounds in the treatment of type 2 diabetes. After screening the compounds, we obtained 46 compounds with lower binding energies than the positive controls, which are acarbose. Using Lipinski's rule of five, we evaluated the drug-likeness of the compounds and identified 12 compounds that met the criteria. Then, continuing to analyze according to pharmacokinetic and toxicological parameters (ADMET), we obtained 3 compounds including Galangin, Maackiain, and Corylin, that have the potential to be developed into drugs when showing the ability to simultaneously inhibit both enzymes α-glucosidase and α-amylase have positive properties: binding energy is lower than the control, creates many interactions with target proteins in the active site, has drug-like properties, relatively good pharmacokinetic properties and low toxicity. Therefore, further in vitro and in vivo studies are needed to develop these potential compounds into drugs for the treatment of type 2 diabetes.